Students' Perspectives Toward English For Specific Purposes In Economic Faculty Of Muhammadiyah University Of Surakarta - Nur'aini, Nur'aini (2006)
English lesson in university is very important nowadays, because it supports the students' ability in mastering English and to fulfill their necessity toward English itself. In this research paper, the writer wants to analyze the students' perspective toward English for Specific Purposes (ESP), especially in economic faculty, Muhammadiyah University of Surakarta . The writer wants to know the real perspective of economic students toward English for Professional Program taught to them by LC UMS. The writer takes students of economic faculty because they often state that learning English is very important to do, beside most economic books are written in English. The writer analyses the perspective of the economic students from there needs of English for Specific Purposes and takes 60 respondents in her research. The data are taken from the students' answer in questionnaire and interview given, then she analyses the result of the data by grouping and classifying the student's answer. The writer knows that students' need toward English for Specific Purposes can be classified in 3 requirements; occupational requirement, vocational requirement, and the last is academic or professional requirement. Beside they can improve their ability in cognitive domain, affective domain, and psychomotoric domain. Bringing this research paper, the writer hopes that the students' true need will cover and it will be known in a more transparent way and the lecturer can find the right syllabus used to teach them.